Effect of different proportions of brea gum in the functional characteristics of wheat flour starch: impact on the physical quality of bread - LÓPEZ,Estela Patricia (2016)
The aim of this work was to study the changes induced by BG in the behaviour of wheat starch, and observe the influence of these variations on the quality of a basic white bread. The effect of four BG addition levels in the wheat flour functional characteristics (WAI, WSI, and pasting properties) and bread quality (physical parameters, crumb grain structure, moisture and hardness) was investigated. The highest levels of BG (1% and 2%) decreased the peak viscosity, and increased the stability and setback of the flour. This was due to a lower gelatinization of the starch granules, caused by a competition for water between the hydrocolloid and starch. These changes influenced the bread quality. The loaves added with 1% and 2% of BG presented smaller alveoli: this resulted in more compact, hard and less airy crumbs. Nevertheless, the moisture of the samples at 1% and 2% of added gum was higher than the control bread. However, the incorporation of BG at 0.5% did not affect the pasting parameters and bread quality, but increased moisture of crumb, so this concentration would be most recommended for baking, since higher humidity could favour the shelf- life of the product.